2022
DOI: 10.1002/hbm.25832
|View full text |Cite
|
Sign up to set email alerts
|

Zapline‐plus: A Zapline extension for automatic and adaptive removal of frequency‐specific noise artifacts in M/EEG

Abstract: Removing power line noise and other frequency‐specific artifacts from electrophysiological data without affecting neural signals remains a challenging task. Recently, an approach was introduced that combines spectral and spatial filtering to effectively remove line noise: Zapline. This algorithm, however, requires manual selection of the noise frequency and the number of spatial components to remove during spatial filtering. Moreover, it assumes that noise frequency and spatial topography are stable over time,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…The BeMoBIL pipeline (Klug et al, 2022) was used to preprocess and clean the EEG data in the MATLAB (Mathworks, Inc.) toolbox EEGLAB (Delorme and Makeig, 2004). We first downsampled the raw EEG data to 250 Hz, and then removed spectral peaks at 50 Hz, corresponding to power line frequency, using the ZapLine Plus function (Klug and Kloosterman, 2022). Then, we applied the automated rejection function clean_artifacts from EEGLAB to identify noisy channels with ten iterations.…”
Section: Data Processingmentioning
confidence: 99%
“…The BeMoBIL pipeline (Klug et al, 2022) was used to preprocess and clean the EEG data in the MATLAB (Mathworks, Inc.) toolbox EEGLAB (Delorme and Makeig, 2004). We first downsampled the raw EEG data to 250 Hz, and then removed spectral peaks at 50 Hz, corresponding to power line frequency, using the ZapLine Plus function (Klug and Kloosterman, 2022). Then, we applied the automated rejection function clean_artifacts from EEGLAB to identify noisy channels with ten iterations.…”
Section: Data Processingmentioning
confidence: 99%
“…In both cases, significant differences were found in high frequency bands: in the beta band in the SSVEPs study (occipital region, photic driving power response at 20 Hz) and in the gamma band in the VEPs study. It should be noted, however, that the differences in the gamma band seem to be due to differences of the power line artifact around 60 Hz, which should be removed in spectral studies [38][39][40]. As the authors indicated in the limitations of their study, this removal was not performed, so the results should be interpreted with caution.…”
Section: Evidence From Magnetic and Electric Cerebral Activity (M/ Eeg)mentioning
confidence: 98%
“…Frequency-specific noise is removed with Zapline-plus (Klug & Kloosterman, 2022). Zapline-plus is an EEGLAB plugin that removes spectral artifact peaks automatically.…”
Section: Eeg Preprocessingmentioning
confidence: 99%
“…However, parameters can be adjusted if the cleaning does not work as intended. See (Klug & Kloosterman, 2022) for details about the processing and parameter tweaking. This step can be avoided by setting the whole bemobil_config.zaplineConfig field to empty.…”
Section: Eeg Preprocessingmentioning
confidence: 99%